HUBUNGAN ANTARA KEBAHAGIAAN DENGAN ALTRUISME PADA KOMUNITAS MOTOR CB DI SALATIGA - Afif Jauza Suhpatriajati ,; Doddy Hendro Wibowo, (Jurnal Cakrawala Ilmiah, 2024)
The spirit of mutual cooperation and solidarity among motorcycle communities is now rarely encountered. However, there is a CB motorcycle community that still exhibits altruistic behavior, such as when they encounter a fellow CB motorcycle rider whose vehicle has broken down on the road. This phenomenon has prompted researchers to conduct a study aimed at investigating the significance of the relationship between altruism and happiness within the CB motorcycle community in Salatiga. The participants in this study consisted of 50 individuals, selected using saturation sampling technique. The data collection method employed in this research utilized a happiness scale developed based on three aspects proposed by Seligman in 2002, along with the Self-Report Altruism Scale (SRA) developed by Rushton, Chrisjohn, and Fekken (1981). The data analysis technique utilized was Pearson product-moment correlation. From the data analysis, a correlation coefficient of r = 0.604 and a significance value of 0.000 (p > 0.05) were obtained, indicating a significant positive 8relationship between happiness and altruism within the CB motorcycle community in Salatiga. This implies that the higher the level of altruism within the CB motorcycle community in Salatiga, the greater tendency towards happiness they possess. Conversely, lower levels of altruism correspond to higher tendencies towards happiness within the CB motorcycle community in Salatiga.